The production of logistics places in France and Germany: a comparison between Paris, Frankfurt-am-Main and Kassel. (1st April 2019) - Barbier, Clément; Cuny, Cécile; Raimbault, Nicolas
Abstract : Logistics is now a key concept for the analysis of the transformations of global capitalism and a central perspective for understanding the changing power relations within global production networks. Furthermore, the development of logistics relies on the construction of thousands of warehouses and terminals that are essential nodes in the circulation of goods. The production of these logistics zones entails negotiations and coalitions between local authorities and different local and global firms, and structures the everyday life of logistics workers. The aim of this article, therefore, is to analyse the production of logistics areas at metropolitan and local scale, through a comparison between Paris (France) and Frankfurt-am-Main and Kassel (Germany). Based on an interdisciplinary approach combining urban sociology, urban geography and political science, it reveals that the production of logistics places is primarily the outcome of local negotiations and legitimisation processes in which the logistics real estate investments of globalised financial markets are embedded.